Measles Maternal Antibodies With Low Avidity Do Not Interfere With the Establishment of Robust Quantity and Quality Antibody Responses After the Primary Dose of Measles, Mumps, and Rubella Vaccine Administered at 12-Months of Age. (23rd October 2019) - Collins, Cathleen A; Gelinas, Laura; Yasukawa, Linda L; Audet, Susette; Abu-Raya, Bahaa; Turvey, Stuart E; Beeler, Judy A; Kollmann, Tobias R; Gans, Hayley A
Abstract: In this study, we illustrate, for the first time, that preexisting low-avidity neutralizing measles maternal antibodies do not interfere with the development of high concentrations of high-avidity measles antibodies in children immunized at age 12 months. This suggests that the quality of measles maternal antibodies, rather than the quantity, impacts immunogenicity of primary measles immunization.